2010
DOI: 10.1111/j.1478-3231.2010.02230.x
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of Niemann-Pick C1 protein protects against diet-induced gallstone formation in mice

Abstract: Hepatic NPC1 expression is an important factor for regulating the biliary secretion of diet-derived cholesterol as well as for diet-induced cholesterol gallstone formation in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 51 publications
3
11
0
Order By: Relevance
“…While Niemann-Pick C1 (NPC1) is a key component for the intracellular distribution of cholesterol originating from lipoprotein endocytosis and plays a role in biliary cholesterol secretion ( 20 ), ABCG5/G8 directly facilitates cholesterol secretion into the bile. However, the role of ABCG5/G8 in SR-BI-mediated enhancement of biliary cholesterol secretion is currently controversial ( 19,21 ).…”
Section: Ceh Hydrolyzes Sr-bi-delivered Hdl-cementioning
confidence: 99%
“…While Niemann-Pick C1 (NPC1) is a key component for the intracellular distribution of cholesterol originating from lipoprotein endocytosis and plays a role in biliary cholesterol secretion ( 20 ), ABCG5/G8 directly facilitates cholesterol secretion into the bile. However, the role of ABCG5/G8 in SR-BI-mediated enhancement of biliary cholesterol secretion is currently controversial ( 19,21 ).…”
Section: Ceh Hydrolyzes Sr-bi-delivered Hdl-cementioning
confidence: 99%
“…The abdomen was opened, the cystic duct was ligated, and a common bile duct fistula was performed with a polyethylene catheter. Hepatic bile was collected for 30 min, while mice remained hydrated, warm, and stable [22], and then blood, liver, and gallbladder were removed. The liver was immediately frozen at -80°C.…”
Section: Hepatic and Gallbladder Bile Blood And Liver Samplingmentioning
confidence: 99%
“…We have previously shown that NPC1 plays a critical role in controlling the biliary secretion of plasma lipoprotein-derived cholesterol in mice [21,22]. Hepatic NPC1 overexpression by adenovirus-mediated gene transfer increases biliary cholesterol secretion in wild-type mice and cholesterol-fed NPC1 (-/-) mice [21].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations